Implementasi Pendidikan Karakter Anak Usia Dini Al-A'raaf - Rosida Nur Syamsiyati (BUANA GENDER : Jurnal Studi Gender dan Anak, 2018)
Children are the next generation of nation that needs to be stimulated and prepared from an early age. The development of brain cells owned by children from birth will develop optimally if given the appropriate treatment and stimulus according to the stage of growth. One of the things that need to be considered and developed in early childhood is character education, because with a good character the child will grow into a human who has good character, strong and able to face the competition of life so tight. This study aims to describe the implementation of character education in Al-A'raaf Islamic Kindergarten. Data collection was obtained through observation, interview and documentation. Technique examination of data validity used is triangulation technique. Character education in Islamic Kindergarten Al A'raaf is done through four stages: planning stage, implementation stage, assessment stage and development stage.